Safety and Efficacy of Aneurysm Treatment with the WEB: Results of the WEBCAST 2 Study - Pierot, L. (AJNR Am J Neuroradiol, 2017)
BACKGROUND AND PURPOSE: Flow disruption with the Woven EndoBridge (WEB) device is an innovative technique for the endovascular treatment of wide-neck bifurcation aneurysms. The initial version of the device (WEB Double-Layer) was evaluated in the WEB Clinical Assessment of IntraSaccular Aneurysm Therapy (WEBCAST) study, whereas the French Observatory study evaluated both WEB Double-Layer and Single-Layer versions of the device. WEBCAST 2 was designed to evaluate the WEB Single-Layer with Enhanced Visualization. MATERIALS AND METHODS: Patients with wide-neck bifurcation aneurysms for which WEB treatment was possible were included. Clinical data including adverse events and clinical status at 1 month and 1 year were collected and analyzed. A core laboratory evaluated anatomic results at 1 year following the procedure. RESULTS: Ten European neurointerventional centers included 55 patients (38 women; 27–77 years of age; mean, 54.4 ± 10.0 years) with 55 aneurysms. Aneurysm locations were the middle cerebral artery in 25 aneurysms (45.5%), the anterior communicating artery in 16 (29.1%), the basilar artery in 9 (16.4%), and the internal carotid artery terminus in 5 (9.1%). Procedural morbidity and mortality at 1 month were, respectively, 1.8% (1/55 patients) and 0.0% (0/55 patients). Morbidity and mortality at 1 year were, respectively, 3.9% (2/51 patients) and 2.0% (1/51 patients). At 1 year, complete occlusion was observed in 27/50 aneurysms (54.0%); neck remnant, in 13/50 (26.0%); and aneurysm remnant, in 10/50 (20.0%) (adequate occlusion in 40/50, 80.0%). CONCLUSIONS: WEBCAST 2 confirms the high safety and efficacy of WEB aneurysm treatment demonstrated in the WEBCAST and French Observatory studies.